RECURRENT APHTHOUS STOMATITIS RELATED TO PSYCHOLOGICAL STRESS, FOOD ALLERGY AND GERD - Rina Kartika Sari; Diah Savitri Ernawati; Bagus Soebadi (Odonto : Dental Journal, 2019)
Background: Recurrent Aphthous Stomatitis (RAS) is inflammation in oral mucosa characterized by recurrent single or multiple ulcers that usually affected in non keratinized mucosa. Etiology RAS is unknown but psychological stress, allergy, and gastrointestinal disease can be predisposing factors Case Management: A 23rd years old complained recurrent oral ulcer with free ulcer period for 3-5 days. The patient had a history of food allergy, GERD and psychological stress. Intraoral examination showed recurrent multiple ulcers in variation site of the mouth. DASS 42 screening showed high stress and high anxiety. Skin Prick Test showed positive allergy to kapok, beef, chicken, cow milk, white egg, duck egg, shrimp, cob fish, milkfish, chocolate, and peanut. Ulcers treated with nonsteroid antiinflammation Aloe Vera gel and stress management by reading assignment method.Discussion: Psychological stress altered the immune system so oral mucosa prone to inflammation, and make the history of GERD getting worse. Stress causes cortisol secretion that changes the imbalance of proinflammatory and antiinflammatory cytokines. Oral mucosa becomes more susceptible to hypersensitivity. In addition, stress decreased oral and esophageal mucosa resistance to GERDConclusion: RAS triggered by psychological stress, allergy, and GERD. Treatment of RAS is by elimination predisposing factors to prevent recurrence.